Perbandingan Pemberian Hiperoksigenasi Satu Menit DAB Dua Menit pada Proses Suction terhadap Saturasi Oksigen Pasien Terpasang Ventilator - Teti Hayati; Busjra M Nur; Fitrian Rayasari; Yani Sofiani; Diana Irawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to identify the effect of 1 minute hyperoxygenation on the suctioning process on oxygen saturation of patients with mechanical ventilators. Quasi experimental research design pre-post test with control group design. The results showed oxygen I saturation before median hyperoxygenation 97 min 95-99, after median hyperoxygenation 99 min 98-100 with p value 0.05. While in the intervention group II before median hyperoxygenation 97 min 95-100, after median hyperoxygenation 99 min 95-100, with p value 0.05. In conclusions there were significant differences in oxygen saturation before and after 1 minute hyperoxygenation administration. Keywords: Hyperoxygenation, Suction Process, Oxygen Saturation, Ventilator